S2k Guideline – Merkel cell carcinoma (MCC, neuroendocrine carcinoma of the skin) – Update 2022 - Becker, Jürgen C.; Beer, Ambros J.; DeTemple, Viola K.; Eigentler, Thomas; Flaig, Michael; Gambichler, Thilo; Grabbe, Stephan; Höller, Ulrike; Klumpp, Bernhard; Lang, Stephan; Pföhler, Claudia; Posch, Christian; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Summary Merkel cell carcinoma (MCC, ICD‐O M8247/3) is a rare, malignant, primary skin tumor with epithelial and neuroendocrine differentiation. The tumor cells share many morphologic, immunohistochemical, and ultrastructural features with cutaneous Merkel cells. Nevertheless, the cell of origin of MCC is unclear. MCC appears clinically as a reddish to purple spherical tumor with a smooth, shiny surface and a soft to turgid, elastic consistency, usually showing rapid growth. Spontaneous and often complete regressions of the tumor are observed. These likely immunologically‐mediated regressions explain the cases in which only lymph node or distant metastases are found at the time of initial diagnosis and why the tumor responds very well to immunomodulatory therapies even at advanced stages. Due to its aggressiveness, the usually given indication for sentinel lymph node biopsy, the indication of adjuvant therapies to be evaluated, as well as the complexity of the necessary diagnostics, clinical management should already be determined by an interdisciplinary tumor board at the time of initial diagnosis.